Influence of the degrees of polymerization of cellulose on the water absorption performance of hydrogel and adsorption kinetics. (October 2019) - Li, Heng-Xiang; Wang, Qun; Zhang, Luming; Tian, Xin; Cao, Qing; Jin, Li'e
Abstract: The cellulose with different degrees of polymerization (DPs) was successfully prepared and applied to synthesize a series of superabsorbent hydrogel (SAH) by grafting polymerization. Cellulose could be partly degraded by the combined effect of ultraviolet (UV) irradiation and sodium hypochlorite (NaClO). The DPs of cellulose decreased by 21% under this pretreatment method. The quantity of water absorption (Q) of SAH derived from the cellulose with different DPs was evaluated. Results indicated that the DPs of cellulose and the Q values of SAH had a good linear relationship when DPs ranged from 101.5 to 195. The Q value increased linearly when DPs decreased. The Q values of SAH synthesized from the cellulose (II), produced after the combined effect of UV and NaClO, were 328 and 129 g/g in distilled water and 0.9 wt% NaCl solution, respectively. The kinetic mechanism for the water absorption of SAH was efficiently described by the second-order model. This work can provide a guide for SAH synthesis based on DPs of cellulose. Graphical abstract: Cellulose, which is used to synthesize superabsorbent hydrogel, can be produced with different degrees of polymerization through the combined effect of sodium hypochlorite and ultraviolet irradiation.Image 1 Highlights: The DPs of cellulose decreased by 21% with the combined effect of UV irradiation and NaClO. There is a linear relationship between DPs in the range of 101.5–195 and the Q value. The Q value increases linearly when DPs decreases in the scope of 101.5 and 195. SAH has a good capacitor of water absorption (129 g/g in 0.9 wt% NaCl solution and 328 g/g in distilled water).